العرف وتطبيقاته المعاصرة في شركة المساهمة - رسولي، مهرزاد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This research aims to study the impact of “al-'Urf” on Joint Stock Company and its contemporary applications. It consists of four chapters: the first chapter talks about methodological approaches, while the second and third chapters discuss the theoretical aspects of the study by applying inductive and analytical methods and introducing al-'Urf and its variety. It then traces evidences of al-'Urf's validity in Islamic Law as well as in Positive Law. These two chapters also discuss the definition of company with factors of its legitimacy in Islamic Law according to the Qurān, Sunna, Ijma' and Reason. In addition, the definition and emergence of Joint Stock Company are studied here. The fourth chapter is devoted to the practical side of the study. With the use of a comparative analytical method, it shows the impact of al-'Urf on the creation of this type of company in general and its impact on the formulation of the company's contract and its management and the actions of each partner in particular. It then shows the effect of al-'Urf in determining the character and continuity of the company and its functions. Furthermore, the study shows the impact of al-'Urf on the provisions of some of the stocks issued by the company through statement of their jurisprudence regulations. All these are done after introducing, categorising and determining how to take possession of and how to value these stocks through discussion and preference according to “valid 'Urf”.